(untitled) (Journal of the College of Languages (JCL), 2014)
Praise be to Allah , the Lord of Heavens , Who revealed His Scripture in plain Arabic, and prayers and peace be upon the Master of all creatures and the chosen one , Muhammad (PBUH).Pushkin was known as a poet in Russia, the sun of its poetry that set, the father of the Russian literature and the founder of its literary language. When he published his poems, trying to express his inner poetic feelings and creative visions, he presented them with creativity and special touch. The reason behind the selection of Pushkin as the subject of this study is that he was affected by Islam and Arabs. For the purpose of this study, the dissertation has been divided into introduction and three chapters; each chapter includes two topics. In the introduction, the history of Russian literature is presented up to the Pushkin period with reference to his role in the Russian literature. Pushkin tried, through the influence of the Holy Qur’an, to introduce himself to the universality of literature, make his poetic voice be heard, and go beyond the limits of Russia and Europe through his expression of some of the ideals people share without being restricted to one culture rather than another; the Holy Qur’an has this ideal universal outlet to achieve such a goal.Each nation has a national heritage which represents an inspiration to Pushkin, notably, the heritage of the Islamic nation that he integrated into his national heritage to represent an enrichment to his poetic experience which later became an example for other poets to follow suit.Pushkin found that the Holy Qur’an meets an intellectual and artistic need through the Artist’s delicate sense to form new experience guided by the Holy Qur’an.The deep meanings of the Holy Qur’an exercised their effects on Pushkin who, without neglecting at the same time, believes that the Holy Qur’an is based on certain linguistic form and base depending on the translated text that he accessed